ToMRobot 2.0: real mobility mechanism in MANET testbed using mobile robot - Muchtar, Farkhana; Al-Adhaileh, Mosleh; Mohd Nordin, Ili Najaa Aimi; Abdulraheem Zubair, Ajoze; Kumar Singh, Pradeep; Ambar, Radzi; Saheed, Ajibade Lukuman (Springer Nature, 2020)
This paper is a continuation of our previous paper under the same topic, ToMRobot 1.0. Our main goal of developing ToMRobot 2.0 is to improve the ToMRobot 1.0 that we developed earlier. ToMRobot was developed because we think mobile robot technology is more practical than other approaches as a real world mobility mechanism in MANET testbed. But to develop our own mobile robot at low cost and at the same time not complex is very challenging. The challenge is overcome through the use of easy-to-use components, self-built components using 3D printers and the use of mobile robot designs that have proven to be easily developed, cheap and effective. The use of the Robot Operating System (ROS) as the main robot software framework greatly helps to reduce the complexity of developing control system for mobile robot.